Financial Market Efficiency at Low Level - A Standard Study of Jorden Financial Market - Khadidja , Fettouhi (Journal of Research in Finance and Accounting, 2025)
This paper aims to test Jordan's financial market efficiency hypothesis at the weak level, using the general indicator of AMGNRLX for daily data from 01-01-2017 to 29-12-2022, using the natural distribution test and stabilization tests (ADF .PP), self-correlation testing. The study found that the time series does not follow natural distribution and that it does not have the advantage of random walk. This paper also found that the effect of conditional variation is an indication of the inefficiency of the Jordanian market for financial markets at the weak level. The results showed that the thoughtful financial market is inefficient at the weak level during the study period.